(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article is dedicated to the role of the art of Maqom in improving the professional training of future music teachers in the higher pedagogical education system and the enhancement of methodical foundations for its teaching. The research analyzes the pedagogical principles of implementing Maqom examples—considered our national musical heritage—into the educational process, modern interpretations of "master-apprentice" traditions, and issues of developing students’ artistic and aesthetic thinking. The recommendations provided in the article serve to form the professional competence of future specialists based on national musical values.